Requisito legal para los progenitores que se ausentan al exterior, en el derecho de alimentos de niños, niñas y adolescentes, propuesta de reforma del artículo innumerado 25 del código orgánico de la niñez y la adolescencia. - Romero Galarza, Celiano Heriberto (2014)
Let us analyze social and legal way on the major issues that cross children and adolescents with respect to an essential and human right, as is the right to food, a right that has been violated by their own parents to emigrate to another country, which is why we have done this research and consists of the following chapters.